2012
DOI: 10.4162/nrp.2012.6.5.466
|View full text |Cite
|
Sign up to set email alerts
|

The development of a taste education program for preschoolers and evaluation of a program by parents and childcare personnel

Abstract: The change in people's dietary life has led to an increase in an intake of processed foods and food chemicals, raising awareness about taste education for preschoolers whose dietary habits start to grow. This study aims to evaluate the effectiveness and satisfaction of parents and childcare personnel after developing a taste education program and demonstrating it in class. A part of the curriculum developed by Piusais and Pierre was referred for the program. After educating 524 preschoolers in child care facil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Studies show that children dare to try more new foods and dishes when they have worked with sensory training ( 43 , 44 ) and the Sapere method ( 34 38 ). This is in accordance with our results as well as a recently published dissertation from the Netherlands ( 39 ), where both teachers and children (4–12 years) experienced the laboratory learning with sensory exercises as very positive.…”
Section: Discussionmentioning
confidence: 99%
“…Studies show that children dare to try more new foods and dishes when they have worked with sensory training ( 43 , 44 ) and the Sapere method ( 34 38 ). This is in accordance with our results as well as a recently published dissertation from the Netherlands ( 39 ), where both teachers and children (4–12 years) experienced the laboratory learning with sensory exercises as very positive.…”
Section: Discussionmentioning
confidence: 99%
“…Most dietary education programs developed in Korea for children consist primarily of simple nutritional education and culinary activities. In one study, parents and teachers of participating children aged 4-7 years who took five lessons of the taste education program observed a positive change in children's dietary habits; however, the study indicated a need to develop tools to measure effectiveness suitable for the age of the participating children as well as programs with long-term effects [ 15 ]. Therefore, there is an urgent need to provide measures that can promote taste education by highlighting the effects of dietary habit improvement for children in order to improve their long-term physical and mental health and facilitate the development of independent dietary habits.…”
Section: Introductionmentioning
confidence: 99%
“…This lack of knowledge presents a key barrier for the provision of nutrition learning experiences, since providing these experiences typically depends on nutrition knowledge and self-efficacy (Lanigan, 2012). A number of traditional, face-to-face educational programs have been developed that train child care providers to teach children about nutrition (Quintana, Villalobos, & May, 2012; Shon, Park, Ryou, Na, & Choi, 2012). However, these programs may only reach a small number of child care providers.…”
mentioning
confidence: 99%